Soviet Repressive Policy in Rural Areas: Kakheti, 1930s - Simashvili, Tengiz; Tchkadua, Shalva; Shioshvili, Irma; Kakhashvili, Nino ("Intercultural Dialogues" Transactions, 2025)
This study explores the mechanisms and scope of Soviet repressive policies in 1930s Georgia, focusing on the villages of the Telavi Municipality. It is based on archival materials from the Kakheti Regional Archive, which detail the administrative, social, and economic conditions of rural communities under Soviet rule. By the late 1920s, Soviet authorities sought to eliminate private property, dismantle individual farms, and establish collective farms, enforcing deep intervention in all aspects of rural life. Special attention was given to integrating the rural population into collective agriculture and suppressing “socially alien” groups, particularly middle and wealthier peasants. Archival documents show that the revocation of voting rights and inclusion on “blacklists” often depended on the personal judgment of village council chairpersons, affecting merchants, peasants, clergy, and their families. These measures restricted access to education, employment, and social mobility, and forced clergy members to abandon religious duties. Expulsion from collective farms and the requirement to provide “certificates of social status” further reinforced political and socio-economic control. Overall, the archival evidence demonstrates that Soviet repressions in 1920-1930s Kakheti were systematic and ideologically driven, combining political, social, and economic mechanisms, and had a profound impact on rural communities.